Carl Schmitt and the Problem of Poltical Theology - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2011)
When Western liberalism won the battle over fascism and communism, it declared ‘the end of history’. The fall of the Berlin Wall and WTC towers has shaken this illusion to the ground. Carl Schmitt treated WWII as the beginning of the fall of Westphalian system. For this reason Schmitt proclaimed political theology as the means for Western identity’s renewal. This notion coined by the Stoic Panaetius referred to the essential dependence of political and cultural phenomena on religion. Schmitt’s version of political theology showed a way out of crisis and was at the same time incompatible with liberal dogmas of tolerance, political correctness and multiculturalism.